Weter consumption during pregnancy and lactation - Figueroa Damián Ricardo; Beltrán Montoya Jorge; Espino y Sosa Salvador (Instituto Nacional de Pediatría, 2014)
During pregnancy, water is retained partially owing to an increase in vasopressin production. Ingested water is used to produce amniotic fluid. Climate conditions and physical activity, gestational nausea and vomit, and a higher caloric intake, increases water needs; during lactation, more water is needed to produce milk. Dehydration during pregnancy is especially dangerous; it must be avoided. Physiological changes during pregnancy modify water metabolism: blood volume and glomerular filtration rate increase; more water is lost trhough sweating and respiration. Placenta con- tains up to 500 mL of water, and there are between 500-1,200 mL of amniotic fluid. Different studies recommend a total water intake of 2,700-4,800 mL/day during pregnancy, of which 1,470-2,370 should be beverages and water. For the Mexican population, the recommendation is 3,000 mL/day. Based on energy intake and the rule of 1-1.5 mL of water per kcal, water intake must increase in at least 300 mL/day at the beginning of the third pregnancy trimester. During lactation the recommended intake is of 3-3.6 L/ day, depending on age. Obesity and overweight during pregnancy are a major health problem, to which sugary beverages contribute. Water must be considered the best choice for hydration during pregnancy and lactation.